2020
DOI: 10.2147/cmar.s244384
|View full text |Cite
|
Sign up to set email alerts
|

<p>Curcumin Affects Gastric Cancer Cell Migration, Invasion and Cytoskeletal Remodeling Through Gli1-β-Catenin</p>

Abstract: The function of curcumin on the gastric cancer cell line, SGC-7901 is unknown. The present study aimed to observe the effects of curcumin on gastric cancer cells through the Shh and Wnt signaling pathways. Methods: SGC-7901 cells were transfected with si-Gli1 and si-β-catenin siRNA, then cells were stimulated with curcumin and its effects on cell migration, invasion, cytoskeleton remodeling, EMT, apoptosis and cell cycle were investigated by transwell assays, immunofluorescence and flow cytometry assays. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Affymetrix microarray results suggest that cytoskeletal remodeling and the Wnt signaling pathway are the two of the top pathways disrupted by ERp57 silencing in HeLa cells [99]. The present data demonstrate that β-catenin participates in the mechanisms of cell adhesion, cytoskeleton remodeling and the canonical Wnt signaling pathway [100]. Stable knockdown of ERp57 induces β-catenin accumulation and inhibits the migration of HeLa cells [99], and resveratrol can increase the interaction between ERp57 and β-catenin [101].…”
Section: Regulation Of Other Signal Transduction Pathwaysmentioning
confidence: 52%
“…Affymetrix microarray results suggest that cytoskeletal remodeling and the Wnt signaling pathway are the two of the top pathways disrupted by ERp57 silencing in HeLa cells [99]. The present data demonstrate that β-catenin participates in the mechanisms of cell adhesion, cytoskeleton remodeling and the canonical Wnt signaling pathway [100]. Stable knockdown of ERp57 induces β-catenin accumulation and inhibits the migration of HeLa cells [99], and resveratrol can increase the interaction between ERp57 and β-catenin [101].…”
Section: Regulation Of Other Signal Transduction Pathwaysmentioning
confidence: 52%
“…Curcumin can impair both proliferation and metastasis of cancer cells via inducing cell cycle arrest, triggering cytoskeletal remodeling and inhibiting epithelial-to-mesenchymal transition (EMT). In this way, molecular pathways such as Wnt and Shh that are involved in cancer progression, undergo downregulation upon curcumin administration [ 46 ]. The inhibitory effect of curcumin on viability and colony formation of cancer cells is vital for enhancing sensitivity of cancer cells into chemotherapy [ 47 ].…”
Section: Antitumor Activity Of Curcumin: In Vitro In Vivo and CLImentioning
confidence: 99%
“…In addition to MMP downregulation, curcumin also exerts an influence on epithelial-mesenchymal transition (EMT), which is a pivotal event that generates prometastatic cell types in cancers. 47 , 48 It was demonstrated that curcumin inhibits HGF-induced EMT in lung cancer via modulation of c-Met, which functions upstream of PI3K/Akt/mTOR signaling. 49 The potential regulatory axis was further verified in HUVECs treated with curcumin, which had impaired tubular formation ability in vitro.…”
Section: Mechanisms Of Curcumin-mediated Lung Cancer Suppressionmentioning
confidence: 99%